2020
DOI: 10.1101/2020.01.28.923391
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

JAK Inhibitors Suppress Colon Cancer Cachexia-Associated Anorexia and Adipose Wasting in Mice

Abstract: Abbreviations: CX, cachexia; IL-6, interleukin 6; JAK, janus kinase; LIF, leukemia inhibitory factor; rLIF, recombinant leukemia inhibitory factor; STAT3, signal transducer and activator of transcription 3. ABSTRACTBackground: Cachexia (CX), a syndrome of muscle atrophy, adipose loss, and anorexia, is associated with reduced survival in cancer patients. The colon adenocarcinoma C26c20 cell line secretes the cytokine leukemia inhibitor factor (LIF) which induces CX. We characterized how LIF promotes CX-associat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 32 publications
(5 reference statements)
1
5
1
Order By: Relevance
“…The adipocyte fractions were subjected to qRT-PCR, and Adipoq-Cre;-LIFR fl/fl adipocytes demonstrated no detectable mRNA expression of LIFR, verifying disruption of the gene in adipocytes in the adipose tissue of the knockout animals ( Figure 1C). Adipocytes from the LIFR knockout mice also had a significant decrease in IL6 expression compared with littermate controls, which is consistent with our previous findings that LIF increases IL6 expression in a JAK-dependent manner in differentiated adipocytes (Arora et al, 2020). At the protein level, there was a significant reduction in LIFR-a in eWAT of knockout mice compared with controls, with equivalent hepatic levels of LIFR-a in knockout and littermate controls ( Figure 1D).…”
Section: Lif-lifr-a Signaling Induces Adipocyte Stat3 Activation and supporting
confidence: 91%
See 4 more Smart Citations
“…The adipocyte fractions were subjected to qRT-PCR, and Adipoq-Cre;-LIFR fl/fl adipocytes demonstrated no detectable mRNA expression of LIFR, verifying disruption of the gene in adipocytes in the adipose tissue of the knockout animals ( Figure 1C). Adipocytes from the LIFR knockout mice also had a significant decrease in IL6 expression compared with littermate controls, which is consistent with our previous findings that LIF increases IL6 expression in a JAK-dependent manner in differentiated adipocytes (Arora et al, 2020). At the protein level, there was a significant reduction in LIFR-a in eWAT of knockout mice compared with controls, with equivalent hepatic levels of LIFR-a in knockout and littermate controls ( Figure 1D).…”
Section: Lif-lifr-a Signaling Induces Adipocyte Stat3 Activation and supporting
confidence: 91%
“…We have now shown that LIF signals through its receptor LIFR-a to induce STAT3 activation and adipocyte lipolysis in adipose. We previously showed that LIF and other IL-6 family members increase the lipolysis potential of the adipocyte through a JAK-dependent mechanism (Arora et al, 2020). Although we observed an association of STAT3 phosphorylation with LIF and IL-6-mediated lipolysis, there was no evidence that STAT3 was required for IL-6 family cytokine-mediated adipocyte lipolysis.…”
Section: Stat3 Is Required For Lif-and Il-6-mediated Adipocyte Lipolysiscontrasting
confidence: 83%
See 3 more Smart Citations